Heat-transfer-method-based cell culture quality assay through cell detection by surface imprinted polymers - Eersels, Kasper (Langmuir : the ACS journal of surfaces and colloids, 2015)
Previous work has indicated that surface imprinted polymers (SIPs) allow for highly specific cell detection through macromolecular cell imprints. The combination of SIPs with a heat-transfer-based read-out technique has led to the development of a selective, label-free, low-cost, and user-friendly cell detection assay. In this study, the breast cancer cell line ZR-75-1 is used to assess the potential of the platform for monitoring the quality of a cell culture in time. For this purpose, we show that the proposed methodology is able to discriminate between the original cell line (adherent growth, ZR-75-1a) and a descendant cell line (suspension growth, ZR-75-1s). Moreover, ZR-75-1a cells were cultured for a prolonged period of time and analyzed using the heat-transfer method (HTM) at regular time intervals. The results of these experiments demonstrate that the thermal resistance (Rth) signal decays after a certain number of cell culture passages. This can likely be attributed to a compromised quality of the cell culture due to cross-contamination with the ZR-75-1s cell line, a finding that was confirmed by classical STR DNA profiling. The cells do not express the same functional groups on their membrane, resulting in a weaker bond between cell and imprint, enabling cell removal by mechanical friction, provided by flushing the measuring chamber with buffer solution. These findings were further confirmed by HTM and illustrate that the biomimetic sensor platform can be used as an assay for monitoring the quality of cell cultures in time